Effect of Variation in Voltage on the Synthesis of Ag Nanopowder by Pulsed Wire Evaporation. (29th February 2012) - Song, Joon-Woo; Lee, Dong-Jin; Yilmaz, Fikret; Hong, Soon-Jik
Abstract : Nanosized Ag particles were obtained in liquid medium, which is composed of deionized water and sodium hexametaphosphate, using pulsed wire evaporation within hundreds of microseconds from pure initial Ag wire (99.98%), with varying voltage. Changes in powder morphology and microstructure due to change in supply voltage was observed by FE-SEM and HR-TEM, and phase structure of powders was analyzed by XRD. The results revealed that average particle size slightly increased with increasing supply voltage without any impurity and oxide phase, which was explained in terms of addition of stabilizer into the coolant liquid. The experimental results also suggest that addition of sodium hexametaphosphate into the coolant liquid is good for enhancing the dispersibility property of silver nanopowders.